The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jsat.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug abuse: from epidemiology to public policy

Abstract: Prescription drug abuse has reached an epidemic level in the United States. The prevalence of prescription drug abuse escalated rapidly beginning in the late 1990s, requiring a significant increase in research to better understand the nature and treatment of this problem. Since this time, a research literature has begun to develop and has provided important information about how prescription drug abuse is similar to, and different from the abuse of other substances. This introduction to a special issue of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 79 publications
4
87
0
Order By: Relevance
“…Studies examining risk factors of NMPDU have identified specific sociodemographic factors that increase risk such as being male, unmarried, and younger (Huang et al, 2006;McCabe et al, 2005;McHugh et al, 2015;Simoni-Wastila and Strickler, 2004). We extend these findings by identifying not only sociodemographic factors that influenced stages of use but also high-risk groups of cannabis and cigarette frequency.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Studies examining risk factors of NMPDU have identified specific sociodemographic factors that increase risk such as being male, unmarried, and younger (Huang et al, 2006;McCabe et al, 2005;McHugh et al, 2015;Simoni-Wastila and Strickler, 2004). We extend these findings by identifying not only sociodemographic factors that influenced stages of use but also high-risk groups of cannabis and cigarette frequency.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, another study using the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) found sedative, tranquilizer, and opioid users were all more likely to engage in alcohol use/hazardous alcohol use and have an alcohol use disorder . Moreover, studies examining sociodemographic factors have indicated lower socioeconomic status, being unmarried, and lifetime/family history of alcohol/drug use disorders were predictive of problem use, but findings have varied in regard to race/ethnicity (McCabe et al, 2005;McHugh et al, 2015;Simoni-Wastila and Strickler, 2004). Therefore, targeting possible risk factors such as sociodemographics, early-onset and frequency of alcohol, nicotine, and cannabis use has the ability to aid clinicians and researchers in developing more efficacious treatments and interventions for NMPDU.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, substances abuse-related conditions resulted in 307,400 deaths compared to 165,000 deaths in twenty years ago. Among these, the highest numbers were from alcohol abuse-related disorders, which caused 137,500 deaths; opioid abuse-related disorders caused 122,100 deaths, amphetamine abuse-related disorders caused 12,200 deaths, and cocaine abuse disorders caused 11,100 [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid and widespread abuse of prescription medications within the United States from the late 1990s through the mid2000s reached epidemic levels based on several national studies [1]. The largest contributor to this problem has been the use of opioid analgesics for nonmedical purposes.…”
mentioning
confidence: 99%